Surgical site infections in colorectal surgery: a portuguese prespective - Cunha, Tiago (2023)
Background Surgical Site Infections are amongst the most frequent complications in colorectal surgery and are associated with increased healthcare and socioeconomical costs. Methods A retrospective study was undertaken from colorectal surgeries performed between 2011 and 2020. An analysis of annual surgical site infection rates, as well of types of infection was performed. Data of compliance to the Portuguese surgical site infection prevention bundle was collected and analyzed from 2019 and 2020. Results 2345 colorectal surgeries were studied in accordance with HELICS/HAI-Net SSI protocols. Surgical site infection rates varied between 26.35% (2013) and 34.10% (2019), with an average of 30.06%. Overall the most prevalent microorganisms were Escherichia coli (23.79%) e Enterococcus faecalis (21.37%). By infection type the most frequent micoorganisms were Enterococcus faecalis (27.47%) in superfcial, Escherichia coli (25.92%) in deep incisional and Escherichia coli (26.21%) in organ/space surgical site infections. Regarding the compliance rate to Portuguese surgical site infection prevention bundle, results were underwhelming, but it was noted that glycemic control (84.9%) and hair removal avoidance (74.5%) were the individual interventions with better observance. Conclusion Surgical site infection rates in colorectal surgery are still high despite the use of prevention bundles. Targeted bundles may be the answer